O sujeito discursivo da propaganda governamental de serviço: contradições do discurso e efeitos de sentido - Ferreira, Maria Luiza Maciel (2017)
This dissertation analyzes, through the Analysis of Discourse of the French line, the conditions of production of the discourse of the governmental advertising of service and how it acts in the materialization of contradictory discursive practices, producing meanings that simulate “reception” and “adoption”. It thus seeks to understand the production of meaning as a historical and ideological practice, constitutive in discursive formation. The corpus of this research was built on the government propaganda service promoted by the Secretary of State for the Promotion of Peace (SEPAZ / AL), as one of the actions of the “AcolheAlagoas” Project in which the campaign “Welcome your child before drugs adopt him” and presented in stickers and pamphlets, started in March 2014, circulated throughout the state of Alagoas until June 2014. In Analysis of Discourse, the senses and the subjects are constituted at the same time in a process that happens in and by language. In this way, we can understand through analysis the discursive functioning, the mechanisms of social determinations in the processes of signification, and the discursive formations and ideological formations that support the utterances. In order to carry out the analyzes, we used a theoretical course based on authors such as Pêcheux (2006, 2009, 2010), Orlandi (1996, 2000, 2002, 2005), Amaral (2016), Silva (2011, 2015), among others. Thus, government discourse uses propaganda to simulate changes of principles and moral values, for the capitalist mode of production claims ways of living in a consumer society, identified with the ideology of capital, sustained by the discursive formation of the State, which prioritizes and values drug problem as being only the family's responsibility.